Descriptive Knowledge About Breast Cancer and the Importance of Breast Self-Examination Among Women - Oteng, Joseph (Kwaghe International Journal of Sciences and Technology, 2025)
Numerous studies regarding the efficacy of publicly advocated breast self-examination in the literature have suggested that it could contribute to an early diagnosis of breast anomalies and increased survival rates. Method: A community-based cross-sectional research design with a mixed methods approach was utilized among 384 women aged 18 - 49 years in the Chereponi district. Multistage sampling technique with a structured questionnaire and Key Informant Interviews for data collection. data were analysed using the SPSS and NVIVO. Results: The research work showed that the participants were abreast with Breast self-examination (BSE) techniques. And that majority of our respondents have a significantly positive impression of BSE. This tallies with the outcome of a study on affected perception of BSE among female secondary school teachers with high perception of BSE (95.5% in the study) by 95.6% of the respondents. Thus, it was also observed that the respondents gave a mean response of 4.04 (SD 0.884), indicating an average but strong sense of knowledge pertaining to where they could seek additional support. Conclusion: It is evident that the majority of the respondents view breast self-examination (BSE) as a significant component of the entire health care regime and also believe the regular practice of BSE can aid greatly in the early detection of breast cancer thereby increase the chances of early cure and furthermore have good confidence in their ability to examine themselves properly.